ETHODOLOGY FOR DEVELOPING STUDENTS’ INTEGRATED PROFESSIONAL-COMMUNICATIVE COMPETENCE IN EMI (ENGLISH-MEDIUM INSTRUCTION) SETTINGS IN HIGHER EDUCATION (The Journal of Interdisciplinary Human Studies, 2026)
This study investigates a methodology for developing integrated professional-communicative competence among university students in English-Medium Instruction (EMI) settings. As the global expansion of EMI programs in higher education accelerates, the dual challenge of simultaneously mastering disciplinary content and developing advanced English-language proficiency has become a critical pedagogical concern. Employing a quasi-experimental design, this research involved 80 third-year undergraduate students at a university in Tashkent, Uzbekistan, divided into an experimental group (n = 40) receiving an integrated Content-Language-Professional (CLP) instructional methodology and a control group (n = 40) following conventional EMI instruction. Data were collected through pre- and post-tests measuring disciplinary knowledge, communicative competence, and professional-communicative task performance over one academic semester (16 weeks). Results demonstrated that the CLP methodology produced statistically significant gains across all three dimensions, with the experimental group outperforming the control group on the integrated competence measure (t(78) = 4.62, p < 0.001, d = 1.03). Qualitative interview data revealed that students in the experimental group reported greater confidence in using English for discipline-specific professional communication. These findings suggest that purposefully designed integrative methodologies can effectively address the content-language gap in EMI programs and have implications for curriculum design, teacher training, and EMI policy in expanding-circle contexts.
Keywords: English-Medium Instruction, EMI, professional-communicative competence, content-language integration, higher education, CLIL, curriculum design.